2019
DOI: 10.1111/liv.14199
|View full text |Cite
|
Sign up to set email alerts
|

HCV reinfections after viral clearance among HIV‐positive patients with recent HCV infection in Taiwan

Abstract: Background: Higher rates of hepatitis C virus (HCV) reinfection after viral clearance have been well described among HIV-positive men who have sex with men (MSM) in Europe. The epidemiology of HCV reinfection, however, has rarely been investigated among HIV-positive patients in Asia-Pacific region. Methods: We retrospectively identified HIV-positive patients with recent HCV infection who had cleared their primary infection, either spontaneously or via treatment, between January 2011 and May 2018. All included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…HCV can be detected in the rectal fluid, and traumatic sex and prolonged sexual contact with HCV-infected rectal fluid may increase the risk for HCV transmission [26]. The findings of our matched cohort study, similar to those of our previous investigation of HCV reinfections after viral clearance among HIV-positive patients [27], have important implications in terms of prevention and testing strategies for HCV transmission. DAA treatments had not been reimbursed by the National Health Insurance, Taiwan, until 2017, before which time patients with chronic HCV infection had to be referred to hepatologists for treatment with pegylated interferon and ribavirin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…HCV can be detected in the rectal fluid, and traumatic sex and prolonged sexual contact with HCV-infected rectal fluid may increase the risk for HCV transmission [26]. The findings of our matched cohort study, similar to those of our previous investigation of HCV reinfections after viral clearance among HIV-positive patients [27], have important implications in terms of prevention and testing strategies for HCV transmission. DAA treatments had not been reimbursed by the National Health Insurance, Taiwan, until 2017, before which time patients with chronic HCV infection had to be referred to hepatologists for treatment with pegylated interferon and ribavirin.…”
Section: Discussionsupporting
confidence: 85%
“…Second, our estimates of incidence rate of HCV seroconversion could be biased by the frequency and targeting of the HCV testing. Adherence to the national guidelines for HCV screening may vary, and HIV-treating clinicians may be prone to adopting symptom-driven testing strategies, which might not be sensitive enough to identify HCV transmission in the key populations [27]. Despite a high association between syphilis acquisition and HCV seroconversion, the testing strategy that was prompted by recent STIs might still miss a substantial proportion of HCV infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence remains inconclusive as to whether people who spontaneously clear HCV have a higher reinfection rate than patients who achieve SVR or vice versa. In our study, reinfection rate among people with spontaneous clearance was more than twice that of people who had achieved SVR (2.74/100 vs. 1.03/100 PYs), consistent with findings from our earlier study during the interferon era 22 and a study of people with HIV/HCV coinfection in Taiwan which reported a higher reinfection rate among people with SC compared to people with SVR (10.2/100 vs. 7.9/100 PYs) although the difference was not significant, reportedly due to small sample size 23 . Two notable studies 2,3 however, have reported contradictory results.…”
Section: Resultssupporting
confidence: 90%
“…The overall crude reinfection rate for the pooled data was 2.8 cases per 100 PY (95% CI 0.8 to 6.3). Table 1 shows that only the Huang (2019) study had [ 21 ] a reinfection rate greater than 5 per 100 PY, and this study only analyzed recurrence (no differentiation between relapse and reinfection); five studies had rates under 2 per 100 PY. Only the Latham (2019) study compared participants using and not using OST services, and found a lower rate of reinfection (0.6 cases per 100PY for OST recipients and 1.9 cases per 100PY for non-OST recipients).…”
Section: Resultsmentioning
confidence: 99%
“…No report included background information on recruitment methods (e.g., flyer, bus ad, outreach in clinics) or sampling methodologies (e.g., consecutive patients); inquiries for supplemental information yielded one result. Testing intervals ranged from varied or not delineated in three studies [ 21 , 22 , 25 ] to a single testing time point in three studies [ 20 , 23 , 26 ]; only two studies delineated multiple testing time points over a significant follow-up period (2–6 years).…”
Section: Resultsmentioning
confidence: 99%